Tin and Tin Compound Materials as Anodes in Lithium-Ion and Sodium-Ion Batteries: A Review - Mou, Haoyi; Xiao, Wei; Miao, Chang; Li, Rui; Yu, Liming (Frontiers in Chemistry, 2020)
Abstract: Tin and tin compounds are perceived as promising next generation lithium (sodium)-ion batteries anodes because of their high theoretical capacity, low cost and proper working potentials.However, their practical applications are severely hampered by huge volume changes during Li + (Na + ) insertion and extraction processes, which could lead to vast irreversible capacity loss and short cycle life. Significances of morphology design and synergic effects through combining compatible compounds and/or metals together in electrochemical properties are analyzed to circumvent these problems. In this review, recent progress and comprehension towards tin and tin compounds used in lithium (sodium)-ion batteries have been summarized and related approaches to optimize the electrochemical performance are also pointed out. Superiorities and intrinsic flaws of above-mentioned materials that affect electrochemical performance are discussed, aiming to provide a comprehensive understanding towards tin and tin compounds in lithium(sodium)-ion batteries.